PEMODELAN DEBIT SUNGAI MENGGUNAKAN SOIL AND WATER ASSESSMENT TOOL DI SUBDAS MAMASA - Irlan, Irlan; A, Widyanti Utami; Rosmaeni, Rosmaeni; Samsu, Andi Khairil A.; Irundu, Daud; Mas'ud, Emban Ibnurusyd (Jurnal Eboni, 2023)
ABSTRACT Issues related to watershed have received primary attention in the past few decades. The hydrological conditions of the watershed area are considered crucial as a source of life. In efforts to achieve sustainable watershed management, understanding the complex hydrological dynamics is very important. The objective of this research is to simulate river discharge using the Soil and Water Assessment Tools (SWAT) model. This study was conducted in the Mamasa Sub-watershed area. The results show that the river discharge in the Mamasa Sub-watershed has increased as it approaches the outlet (downstream) through the accumulation of discharge in larger order rivers. The Mamasa Sub-watershed also experiences a trend of increasing average annual discharge at a rate of 0.74 m3/s per year. Improvement in the discharge simulation results was achieved through a calibration process using 11 parameters. The calibration results indicate that the calibrated discharge has a higher R2 value compared to the initial simulation discharge, showing that the model calibration successfully improved the quality of the expected discharge results to reach 79.50 percent. However, the calibration results still have a low R2 value, influenced by the selection of appropriate parameters and accurate observational data. Keywords: Modeling, River discharge, SWAT, Watershed